IMPROVING THE CONCENTRATION OF CHILDREN AGED 5-6 YEARS THROUGH BEADING ACTIVITIES AT KARTIKA II-3 KINDERGARTEN - Syarifah Aliyah Herdady; Yuni Dwi Suryani (Department of Early Childhood Education, Universitas Bina Bangsa Getsempena, 2026)
This study aims to improve the concentration ability of children aged 5-6 years through beading activities at TK Kartika II-3, Palembang City. Based on the results of the initial observation, out of 15 children, 14 experienced difficulties in maintaining focus, were easily distracted, and did not complete task thoroughly. To address this issue, the study employed Classroom Action Research using the Kemmis and McTaggart model, which consists of the stages of planning, action, observation, and reflection. The research was conducted in two cyles with a total of 16 meeting. Beading activites were selected because the involve choosing colors, selecting shapes, listening to instructions, following patterns, and threading beads onto strings, which can train children‘s focus and accuracy. The research subjects consisted of 15 children from group B1. Data were collected through observation, documentation, and assessment sheets the results showed an improvement in children‘s concentration abilities from the pre-cycle to Cycle II. In the pre-cycle, most children were in the “beginning to develop“ category, which increased to 60% in the “developing as expected“ category in Cycle I and reached 80% in the “very well developed“ category in Cycle II. These findings indicate that beading activities are effective in improving early childhood concentration as they provide engaging, active, and varied learning experiences.